SUCCESSFUL MANAGEMENT OF PREPARTUM CERVICO-VAGINAL PROLAPSE IN A GIR COW BY NEW ZEALAND TECHNIQUE - A CASE REPORT - ARUNPANDIAN, J; KUMAR, BRIJESH; N , Srivastava; M, GANESAN; B, NEETHU; KUJUR, ANJU (The Indian Journal of Animal Reproduction, 2021)
2.5 years old, four months pregnant Gir cross-bred primiparous heifer was referred with the history of having a prolapsed mass for the past three days. On clinical examination, a certain part of the prolapsed mass was found to be dry and necrosed. On rectal examination, the animal was found to be approximately five months pregnant. The prolapsed mass was cleaned with a non-irritant solution followed by topical application of antiseptic lotion. After removal of necrotic portion, the lacerated part was sutured. Since the prolapsed mass was larger than the vaginal canal reduction of prolapsed mass by the New Zealand technique was carried out. Horizontal mattress suture was applied following the reduction of prolapsed mass. The intravenous fluid therapy, antibiotics, and anti-inflammatory drugs were given for one week. The cow had an uneventful recovery.